Thinking Style Pattern Among Design and Technology Teachers in Malaysia - Shanty Saien; Tee Tze Kiong; Jailani Md Yunos; Yee Mei Heong; Mimi Mohaffyza Mohamad; Widad Othman; Mohamed Nor Azhari Azman; Zaliza Hanapi; Nurulwahida Azid (2019)
critical thinking style of Design and Technology (DT) teachers across Malaysia. A total of 367 teachers are involved he instrument known as YPCreative-Critical Test which consist of 34 items. This instrument was develop using Google Form and been send out to the respondent through email, Facebook, WhatsApp, Telegram and Instagram application to ease the teachers to respond online. The data then analyzed using descriptive statistic and inferential statistics. The finding from this study showed that nearly half of the DT teachers having balance thinking style. Creative thinking style has 35.4% of the total while critical thinking style 19%. None of our teachers has superior thinking style. The independent t-test result shows there is no significant difference thinking styles among DT teachers in gender.